ECONOMIC PARAMETERS OF OPTIMAL PRODUCTION STRUCTURE IN IRRIGATION CONDITIONS - Sredojević, Zorica; Gajić, Boško; Živković, Dragić (Economics of Agriculture, 2006)
As the system of plant production depends on the farm production orientation, but the wider area as well, by properly formulated organization, economic and technical parameters it could be achieved the following goals: maximal utilization of production potentials; land fertility preservation and increase; fulfillment of the needs for livestock husbandry, then for processing capacities in the food processing industry; achievement of maximal financial result per area unit; choice of appropriate irrigation system together with its full effectiveness, profitability and achievement of ecological optimum etc. By introduction of intensive vegetable crops in irrigation conditions as well as higher share of industrial crops, there are made foundations for better utilization of the food processing industry capacities, then for development of intensive livestock husbandry as well as creation of possibility for replacement of fertilizers by manure. Respecting economic advantages of irrigated production, in this paper it is given the methodological procedure for establishment of economic parameters concerning optimal production structure.